Aggregate Information and Organizational Structures - Gorkem Celik; Dongsoo Shin; Roland Strausz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We study information flows in an organization with a top management (principal) and multiple subunits (agents) with private information that determines the organization's aggregate efficiency. Under centralization, eliciting the agents' private information may induce the principal to manipulate aggregate information, which obstructs an effective use of information for the organization. Under delegation, the principal concedes more information rent, but is able to use the agents' information more effectively. The trade-off between the organizational structures depends on the likelihood that the agents are efficient. Centralizing information flows is optimal when such likelihood is low. Delegation, by contrast, is optimal when it is high.
Keywords: D86; L23; L25; 330; agency; aggregate information; organization design